Potential Consequences of Abandonment in Preschool-Age: Neuropsychological Findings in Institutionalized Children - Cardona, Juan F. (Behav Neurol, 2012)
Objective: Several longitudinal studies had shown that early deprivation and institutionalization during the first six months of life affects the emotional, cognitive, social and neurophysiologic development. Nevertheless, our understanding of possible similar effects of delayed institutionalization, in preschool-age remains unclear to this day. The goal of this study is to evaluate the cognitive performance of institutionalized children with history of preschool-age physical abandonment. Method: 18 male institutionalized children with history of abandonment during the preschool-age (2–5 years old) and comparison group matched by age, handedness, gender, educational and socioeconomic level were tested on multiple tasks of attention, memory and executive functions. Results: We found a cognitive impairment in the institutionalized children in several measures of attention, memory and executive functions. This is the first report of cognitive impairment related to late abandonment and institutionalization effects (after 2 years old), extending the already known effects on early institutionalization. Conclusions: This preliminary study suggests that environmental factors including abandonment and institutional care, can affect not only the infancy period, but also the preschool period providing new insights into our understanding of neurocognitive development.